STRATEGI PENGEMBANGAN POTENSI DESA YEH EMBANG KANGIN SEBAGAI DESA WISATA BERBASIS BUDAYA DI KECAMATAN MENDOYO KABUPATEN JEMBRANA - I Gusti Made Dwi Candra Anggara; Pande Putu Wulandari (Journal of Tourism and Interdiciplinary Studies, 2023)
This research examines the development strategy of Yeh Embang Kangin Village as a tourism village in Jembrana district. The objectives are to identify the potential and the internal, as well as the external conditions of Yeh Embang Kangin Village, and to analyze the development strategy of Yeh Embang Kangin Village as a tourism village. Data collection was done by observation, interviews and documentation. Methods undertaken in this study were analyzed by analytical chain processes described qualitatively. The results showed that lack quality of human resources in developing tourism potential in Yeh Embang Kangin village, made the tourist attractions still not running optimally. This research recommends four strategies to optimize the development of tourism in Yeh Embang Kangin Village. The strategies are tourism product development, security and comfort improvement, development of tourism infrastructure, and human resource development.